A review of Capezoum Adlbauer, 2003 (Coleoptera: Cerambycidae) with the description of two new species from the Succulent Karoo ecosystem in South-Africa - Maquart, Pierre-Olivier; Vitali, Francesco; Bate, Riana (Zootaxa, 2021)
Capezoum Adlbauer, 2003 is known only from male specimens. Herein, we describe two new species: Capezoum richardi sp. nov. and C. brunneopunctatus sp. nov., from the Northern Cape region in South-Africa. The discovery of these new species, one of them represented by both sexes, allowed us to describe the hitherto unknown female. Moreover, the genus is transferred to the tribe Xystrocerini and a key to the species of the genus is provided. Lastly, the position of Mythozoum Thomson, 1878 in Cerambycidae is discussed.